Bean, Broad—Vicia faba L. - James M. Stephens (EDIS)
This document provides an overview of broad beans (Vicia faba L.), detailing their origin, varieties, and cultivation practices. Broad beans, known by various names such as horse bean and fava bean, are believed to originate from the Mediterranean area. The plant is an erect, leafy legume with large, flat seeds and thick pods. Broad beans thrive in cool seasons and require 4-5 months to mature. They are highly nutritious, containing 23% protein, and can be used as a cooked vegetable or livestock feed. However, caution is advised due to the potential occurrence of favaism in certain regions. Original publication date April 1994.